The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1128/aac.42.3.521
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Evaluation of Factors Associated with the Development of Bacterial Resistance in Acutely Ill Patients during Therapy

Abstract: The selection of bacterial resistance was examined in relationship to antibiotic pharmacokinetics (PK) and organism MICs in the patients from four nosocomial lower respiratory tract infection clinical trials. The evaluable database included 107 acutely ill patients, 128 pathogens, and five antimicrobial regimens. Antimicrobial pharmacokinetics were characterized by using serum concentrations, and culture and sensitivity tests were performed daily on tracheal aspirates to examine resistance. Pharmacodynamic (PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
246
0
9

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 474 publications
(257 citation statements)
references
References 25 publications
(41 reference statements)
2
246
0
9
Order By: Relevance
“…The targets were based on prior studies of the PK and pharmacodynamic characteristics of aminoglycosides [12][13][14] and are consistent with the pivotal studies for tobramycin solution for inhalation in cystic fibrosis [14]. We chose a reference MIC of 256 lg/mL because this was the highest amikacin MIC for Pseudomonas aeruginosa and Acinetobacter spp.…”
Section: Study Endpointsmentioning
confidence: 99%
“…The targets were based on prior studies of the PK and pharmacodynamic characteristics of aminoglycosides [12][13][14] and are consistent with the pivotal studies for tobramycin solution for inhalation in cystic fibrosis [14]. We chose a reference MIC of 256 lg/mL because this was the highest amikacin MIC for Pseudomonas aeruginosa and Acinetobacter spp.…”
Section: Study Endpointsmentioning
confidence: 99%
“…Antibacterial agents do not represent a medical risk when used appropriately. However, the frequent and inappropriate use of antibacterial agents might have profound adverse health outcomes for individuals and society [5][6][7][8][9]. Many people tend to store different types of antibacterial agents at home for future self-medication [10].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, animal and human studies have shown that the pharmacodynamic parameter that best correlates with bacteriological eradication is AUC 24 /MIC (Table 1) [3,6,10,16•,17•,18-22,24]. Further, the pharmacodynamic parameter Cpmax/MIC also correlates with bacteriological eradication and prevention of the development of resistance on therapy (Table 1) [2••,3,10, [19][20][21]. Agents in a third group of antibiotics, including azithromycin, exhibit a time-dependent bacterialkilling pattern and prolonged persistence effects; in vitro and animal studies have shown that AUC 24 /MIC is the parameter best linked to bacteriological eradication and outcome ( …”
Section: Pharmacokinetic/pharmacodynamic Antibiotic Relationshipsmentioning
confidence: 96%
“…These authors also have shown that achieving a AUC 24 /MIC ratio of at least 100 is required to prevent the development of resistance on therapy [20].…”
Section: Antibiotic Pharmacodynamic Relationships In Respiratory Infementioning
confidence: 96%
See 1 more Smart Citation